Characterization of Boar Studs in Brazil - Bennemann,Paulo Eduardo (2020)
ABSTRACT: Understanding the flow of processes in swine production systems and how they work is fundamental to improving reproductive performance. We surveyed 32 boar studs in Brazil, representing 61.53% of the total in the country. Commercial lines were the most common breed (59.38%) used in the studs. Individual pens and stalls were the most commonly used as housing system (71.9%), and 81.25% of the studs reported having some form of thermal control system. For most of the studs (62.51%), average weekly sperm concentration was higher than 200 million cells per mL. Also, for most studs (71.88%) average weekly ejaculate volume was more than 250 mL. In 46.88% of the studs each ejaculate yielded 26 to 40 semen doses. In 6.25% of the studs, 3.5 billion sperm cells per dose were used for artificial, intracervical insemination. Sperm concentration in 46.88% of the studs was determined using a computer-assisted system analysis. The assessment of sperm quality was conducted using morphology, concentration, and microbiological testing. Employees working on semen collection had formal education of elementary/middle school (34.38%) and high school (37.5%). Most of the laboratory technicians had frequented high school (75%). The most time-consuming task was semen processing, taking 16 to 25 h a week (46.8%) and 6 to 10 h was allotted for the cleaning of stud facilities (46.8%). The data collected in the present study allow greater knowledge of this important part in the pig production chain in Brazil.